Game, set and message - Charl Durand Charl Durand (Communicare)
Sport is just not cricket any more. Seems like just yesterday the only way we Johannesburg folk could follow a nail-biting international rugby test happening at Newlands in Cape Town was by listening to Gerhard Viviers' commentary on Afrikaans radio. I remember my grandfather sitting on the stoep, a map of the playing field drawn on a large sheet of paper on his lap, plotting team moves, attacks, defences and scores, as Gerhard's staccato commentary poured through the speakers of an old Grundig medium wave receiver next to him; definitely a case of what Marshall Mcluhan would call 'a very cool medium'. In the days before mass media, the sports message sent to those absent from the action on the field contained little else of fact other than a score, and a winner, and the message reached the receiver a day, a week or a month later. Messages then gradually expanded to include match details and perhaps a grainy photograph or two as newspapers started reporting on sport. Radio revolutionised sport in that it provided the impetus for the massification of sport as teams and individuals developed followings, and the concept of 'the fan' was born. Radio truly took sports matches beyond the stadium gates for the first time.